Investigation of the binding modes of a positively charged pillar[5]arene: internal and external guest complexation. Issue 4 (3rd January 2017) - Gómez-González, Borja; Francisco, Vitor; Montecinos, Rodrigo; García-Río, Luis
Abstract : The selective binding behavior of a trimethylammonium-derived pillar[5]arene towards different guests in aqueous media and under neutral conditions is reported. Abstract : The selective binding behavior of a trimethylammonium-derived pillar[5]arene towards different guests in aqueous media and under neutral conditions is reported. Although it is known that this macrocycle has the capability to form complexes with guests, we anticipate that the intrinsic pillar shape of the macrocycle with two positively charged rims should allow a diversity of binding modes. The three guests were selected based on their charge and size. The inclusion binding modes and the affinity of the macrocycle to form host–guest complexes were determined by ITC and NMR techniques. We reveal the ability of a cationic water soluble pillar[5]arene to effectively complex two guest molecules, one in each rim, evidencing the diversity of binding modes. Two different structures for 1 : 1 and three for 1 : 2 complexes are reported showing the pillararene ability for internal/external binding.